A GIS Analysis of East Asian Care Gaps in Residential and Assisted Living Facilities in Vancouver, Canada. Issue 2 (3rd April 2019) - Walker, Blake Byron; Canham, Sarah L.; Wister, Andrew; Fang, Mei Lan
Abstract: Residential care and assisted living services provide support to seniors who may not have the ability to live independently. However, East Asian residents often do not have sufficient access to culturally specific activities, which may result in psychosocial stress and isolation. This study presents a geographic analysis method to evaluate spatial distribution of culturally tailored senior care facilities in Metro Vancouver. We identify geographical disparities, indicating that many East Asian seniors have poor local access to a culturally tailored facility. We recommend the use of geographical analysis techniques to improve the analysis and planning for senior care in an increasingly diverse population.